Desain sepeda motor listrik dengan gaya sporty aggressive dalam menunjang program Smart City Kota Surabaya - Yusufa, Muhammad Wildan; Diansyah, Senja Alfakori; Kurniawan, Arie; Maharany, Gunanda Tiara; Syaputra, Eko Agung (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2025)
Smart City is one of Surabaya's programs realized through technological innovation, which connects, monitors, and controls resources to be more effective and efficient in service delivery to sporty sustainable development. The design of urban electric motorcycles with a sporty aggressive style is part of the effort to accelerate the Smart City program in Surabaya, focusing on the Smart Environment & Mobility category. This electric motorcycle design is integrated with futuristic elements and advanced technology to create an environmentally friendly, energy-efficient motorcycle that aligns with the vision of sustainable urban development. The research covers the design process from conceptualization to prototype development, considering ergonomic, safety, and performance aspects. The result is a design concept that not only meets aesthetic and performance standards but also makes a positive contribution to urban environments, in line with Smart City development goals. The practical implications of this research include the potential use of electric motorcycles designed with a sporty aggressive approach to improving environmental quality and enhancing sustainable mobility in Surabaya.